Living in the countryside and studying in the city: the reality of children and young people from a community in Northern Tocantins, Brazil - Yonara Laize Rocha Cruz; Maciel Cover; Cícero da Silva (Universidade Federal do Norte do Tocantins, 2021)
The closure of schools located in rural communities in Brazil by public authorities has been recurrent in the country. Based on the development of a quantitive and qualitative research, characterized as a case study, this work sought to analyze the closure process of a school located in the rural area of ​​the municipality of Tocantinópolis-TO, and its consequences for students and their families. The research corpus consists of semi-structured interviews with social actors in the community (six students, a student's parent, a principal and the municipality's Secretary of Education), in addition to documents. Among the results of the research, it is worth mentioning that in 2018 the number of students who lived in Ribeirão Grande II village and its surroundings and who studied in the urban area of Tocantinópolis totaled 78, and that these students had to travel an average of 15 km daily by bus to the schools in urban area. Of this total, 28 students are between 4 and 10 years old and are enrolled from kindergarten I to 4th grade. Considering the principle that rural people need an education that is in and out of the countryside and that the school should value knowledge, cultural identity, history, as well as the struggles of peasants in training processes, it is important to emphasize the reopening of a school in the community to serve the students who live there.